Different viral genes modulate virulence in model mammal hosts and Culex pipiens vector competence in Mediterranean basin lineage 1 West Nile virus strains - Fiacre, Lise; Nougairède, Antoine; Migné, Camille; Bayet, Maëlle; Cochin, Maxime; Dumarest, Marine; Helle, Teheipuaura; Exbrayat, Antoni; Pagès, Nonito; Vitour, Damien; Richardson, Jennifer P.; Failloux, Anna-Bella; et al. (Frontiers in Microbiology, 2024)
West Nile virus (WNV) is a single-stranded positive-sense RNA virus (+ssRNA) belonging to the genus Flavivirus. Its enzootic cycle involves mosquito vectors, mainly Culex, and wild birds as reservoir hosts, while mammals, such as humans and equids, are incidental dead-end hosts. It was first discovered in 1934 in Uganda, and since 1999 has been responsible for frequent outbreaks in humans, horses and wild birds, mostly in America and in Europe. Virus spread, as well as outbreak severity, can be influenced by many ecological factors, such as reservoir host availability, biodiversity, movements and competence, mosquito abundance, distribution and vector competence, by environmental factors such as temperature, land use and precipitation, as well as by virus genetic factors influencing virulence or transmission. Former studies have investigated WNV factors of virulence, but few have compared viral genetic determinants of pathogenicity in different host species, and even fewer have considered the genetic drivers of virus invasiveness and excretion in Culex vector. In this study, we characterized WNV genetic factors implicated in the difference in virulence observed in two lineage 1 WNV strains from the Mediterranean Basin, the first isolated during a significant outbreak reported in Israel in 1998, and the second from a milder outbreak in Italy in 2008. We used an innovative and powerful reverse genetic tool, e.g. ISA (infectious subgenomic amplicons) to This is a provisional file, not the final typeset article generate chimeras between Israel 1998 and Italy 2008 strains, focusing on non-structural (NS) proteins and the 3'UTR non-coding region. We analyzed the replication of these chimeras and their progenitors in mammals, in BALB/cByJ mice, and vector competence in Culex (Cx.) pipiens mosquitoes. Results obtained in BALB/cByJ mice suggest a role of the NS2B/NS3/NS4B/NS5 genomic region in viral attenuation in mammals, while NS4B/NS5/3'UTR regions are important in Cx. pipiens infection and possibly in vector competence.